The Impact of Fiscal Factors on The Time Spent With Children: a Model Analysis - Kudła, Janusz; Walczyk, Konrad (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Fiscal incentives affect not only fertility, but also the amount of time spent by parents with adolescent children (so called attention). As a consequence the latter can have an indirect impact on the accumulation of human capital in society. Therefore in the paper we apply an economic model of “myopic” parents to analyze the impact of fiscal parameters on time spent for growing up children. The conclusions are based on the simulation in comparative statics calibrated to the actual data. The result indicates that the reaction of families with two children on the children subsidy differs to the reaction of families having only one child. It indicates that some fiscal instruments are vulnerable to the number of children in families, hindering the objectives of social policy focused on human capital accumulation. The fiscal instruments increasing affluence of families stimulate the amount of time spent with children.